Tantangan Pembelajaran di Era Pandemi - Sriawan, Minda; Rudiansyah, Rudiansyah (Jurnal Bahasa, Sastra, dan Budaya, 2022)
The Covid-19 pandemic is very disturbing to the people of Indonesia. The government has strictly ordered all people to stay at home and carry out all activities only from home, one of which is learning activities. This makes students mentally exposed and also a culture of unpreparedness. Learning that was originally face-to-face (offline) now has to switch to online learning. This article contains the challenges faced by the world of Indonesian education in the implementation of online learning. The method used is a literature study by collecting various sources that discuss the challenges of online learning in Indonesia. The results of a literature search show that there are two main challenges of online learning in Indonesia, namely the quality of teachers and infrastructure. The quality of the teacher is related to the ability of the teacher to use information technology in the learning process which is considered very low, influenced by age and laptop ownership. Facilities and infrastructure include internet networks that have not yet reached rural areas, unstable internet networks, and the cost of buying internet quotas.Keywords: Learning; Digital Era; Online Learning; Teacher Quality; Learning Infrastructure